Meta Analisis Valuasi Ekonomi Hutan Dalam Mendukung Kebijakan Konservasi Berkelanjutan - Yurike Yurike; Rica Denis; Yudha Saktian Syafruddin (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2026)
Forests are a natural capital asset that provide various ecosystem services, including forest product provision, climate regulation, biodiversity conservation, water protection, and cultural services. However, various development policies still tend to ignore the total economic value (TEV) of forests, leading to short-term financial gains being the driving force behind land use decisions. This study aims to conduct a meta-analysis of forest economic valuation research to identify the economic value of forest ecosystem services, the factors influencing variations in economic value, and their implications for sustainable conservation policies. The research method used a systematic literature review approach following the PRISMA guidelines, synthesizing various reputable international articles. The meta-analysis results indicate that the economic value of forest ecosystem services is strongly influenced by forest type, valuation method, socioeconomic conditions, ecological characteristics, and the type of ecosystem service assessed. Global studies have shown that integrated ecosystem service valuation yields significantly higher economic value than timber forest product valuation alone. These findings reinforce the point that forest conservation not only provides ecological benefits but also provides long-term economic benefits for communities and governments. Therefore, the results of this meta-analysis can serve as a scientific basis for formulating policies on payments for environmental services, carbon trading, sustainable forest management, and low-carbon development.of economic valuation into forestry policies is necessary to reduce the rate of forest damage sustainably